Implementation of National Movement for the Acceleration of Nutrition Improvement Policy for the First 1,000 Days of Life in Indonesia - Napirah, Muhammad Ryman; Vidyanto, Vidyanto; Rahman, Nurdin; Ningrum, Arum Sekar; Asmawati, Asmawati; Veruswati, Meita (UI Scholars Hub, 2024)
The national movement for accelerating nutrition improvement in the first 1,000 days of life is an effort to strengthen the Indonesian Government's commitment to the national strategic agenda and tackling stunting. This study aimed to determine communication, resources, disposition, and bureaucratic structure in implementing the movement at the Biromaru Primary Health Care (PHC) and Loru Village, Sigi District, Indonesia. The mixed method approach was carried out with informants consisting of several parties from the PHC, health cadres, and the local community through triangulation and questionnaires. The results showed poor communication was inhibited by a lack of community outreach, the attitude of the community’s lack of participation, and the PHC staff’s perceptions (85.14%). There was still insufficient number of health workers as resources (79.73%) who could cover all work areas. While, 75.68% of the health workers considered the disposition to be unfavorable because the incentive budget functioned as an operational budget. Only the bureaucratic structure has been running well, according to 82.43% of PHC staff. Standard operating procedure is required to make the movement run well.